The role of soil moisture on summer climate simulations over southern Africa - Mdoka, Marshall Lison (Department of Environmental and Geographical Science, 2016)
This study aims to increase our perspective of the responses of Southern African climate to soil moisture forcings by drying or moistening the land surface using a regional climate model version 3, RegCM3. The sensitivity and response capabilities to soil moisture perturbations of the model are investigated. This includes identification of regions that may be influenced differently by antecedent soil moisture conditions as well as understand the implications of soil moisture conditions on frequency and intensity of rainfall. Exploratory analyses of soil moisture retention and comparison of climate model parameters with available observations or re-analysis data is done. The study then seeks out the large-scale atmospheric forcings under which the regional climate explicitly responds to perturbations in soil moisture using self-organising map technique. To investigate these underlying processes of atmosphere-soil moisture interactions a series of RegCM3 model experiments utilizing wet, dry and normal soil moisture conditions were designed. The experiments are based on changing the soil moisture field capacity in the RegCM3. The control simulations are run with RegCM3 nested in NCEP/NCAR reanalysis 2 data and using Emanuel convective scheme for the selected six summers (dry seasons - 1991/92, 1994/95 and 1997/98; wet seasons - 1995/96, 1996/97 and 1998/99). September to March simulations are performed with August as the spin-up month. The respective dry and wet soil moisture perturbation simulations are then initialised at field capacities of 25% (wilting) and 75% (saturation) within the land surface model, Bio-sphere Atmosphere Transfer Scheme. From the sensitivity studies, anomalously dry (wet) conditions have positive feedbacks with similar dry (wet) synoptic forcings of the regional climate. Anomalous dry forcing persists for longer and exacerbates the changes in the regional anticyclonic circulation especially during a drought or dry period. Soil moisture perturbations mostly affect the lower troposphere. Surface variables analysed especially surface temperature show strong responses to the soil moisture perturbations under all synoptic forcings but rainfall characteristics are strongly influenced by large-scale synoptic circulations. However, in some areas over southwestern parts of the region a weak feedback which can be either positive or negative depending on geographical and climatological setting has been detected.